2019
DOI: 10.1016/j.fertnstert.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between unexplained recurrent pregnancy loss and 5,10-methylenetetrahydrofolate reductase) polymorphisms

Abstract: Objective: To investigate the relationship between unexplained recurrent pregnancy loss (URPL) and polymorphisms of folate metabolism-related genes. Design: A case-control study. Setting: Urban university-based hospital. Patient(s): Two-hundred and eighteen women with URPL and 264 healthy controls. Intervention(s): None. Main Outcome Measure(s): Fluorescence quantitative polymerase chain reaction examination of sequences of the C677T and A1298C loci of the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…The mild tendency of A1298C in Heterozygous model might attribute to composite C677T and A1298C. Xu [44] has found that compound 677/1298 heterozygous genotype is a risk factor in RPL. In 218 in RPL group and 264 in control group, no composite homozygote genotype appeared; however, patients with composite heterozygote (677CT-1298AC) presented with higher risk compared with the control group (OR, 95%CI 4.996, 1.65-15.129).…”
Section: Discussionmentioning
confidence: 99%
“…The mild tendency of A1298C in Heterozygous model might attribute to composite C677T and A1298C. Xu [44] has found that compound 677/1298 heterozygous genotype is a risk factor in RPL. In 218 in RPL group and 264 in control group, no composite homozygote genotype appeared; however, patients with composite heterozygote (677CT-1298AC) presented with higher risk compared with the control group (OR, 95%CI 4.996, 1.65-15.129).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent pregnancy loss (RPL) is a highly heterogeneous condition and defined as two or more sequential abortions before the 20th week of gestation [1,2]. This condition affects approximately 1-2% of fertile couples, and becomes a common public reproductive concern causing both physical and emotional burdens [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, with 50% of RSA still occurring due to unknown causes, we designate this as unexplained recurrent abortion (URSA) 1 . URSA is an excluded diagnostic disease, and its diagnosis and treatment still face great challenges, although studies have shown that the underlying causes of RSA include systemic endocrine and immune disorders 1,[4][5][6][7][8] . Many scholars are now paying close attention to the gamete and the regulation of maternal-fetal interactions after blastocyst implantation [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%